The Effect of Preservation on the Shelf Life of Laboratory Processed Biscuit (Baghdad Science Journal, 2025)
This study has been conducted to investigate the influence of preservatives(sodium propionate and potassium sorbate) at different levels to extend the storage life of laboratory processed biscuit.The results have shown that When%0.10 sodium propionate was added bacteria and fungi was not found for three months while found in the fourth month of storage.However bacteria and mold didnot grow until the sixth month of storage as %0.20 and %0.30 concentration was used. On the other side as %0.03 potassium sorbate was used,the growth of bacteria was cheched for 3 months and 4 months for molds..When %0.06 potassium sorbate was used no growth of bacterial or mold was found until the sixth month of storage .Three types of bacteria have been appeared in processed biscuit, namely, Staphylococcus aureus, Bacillus cereus, Esherichia coli. In different percentage. and two genera of mold have been found with different rates ,they were Aspergillus and Penicillium.The sensory evaluation of processed biscuit stored for 6 months showed that treatment with %0.30 sodium propionate and %0.10 potassium sorbate were superior as compared to control, they obtained the highest over all acceptance which valued 4.9, 4.7 respectively, while the control treatment obtained 4.1 .